Dynamic optimization of batch diafiltration processes - Fikar, M.; Kovacs, Z.; Czermak, Peter (My University, 2010)
A comprehensive modeling approach is proposed for the dynamic simulation and operation optimization of batch diafiltration processes. We provide a unified technology for water utilization control that addresses generality ver- sus special cases. A rigorous dynamical model of the diafiltration process with concentration-dependent rejections of solutes is developed. We deter- mine the optimal time-dependent profile of the diluant flow for the entire process using dynamic optimization methods. The results show that optimal process operation needs not to be any of the conventional diafiltration con- cepts. The presented optimization technique is a useful tool for improving the performance of a membrane diafiltration process.
Keywords: Membrane filtration; Diafiltration; Mathematical modeling; Dynamic optimization